The role of intrinsic motivation in mediating the impact of auditor characteristics on audit quality in Indonesia - Amlayasa, Anak Agung Bagus; Sudarma , I Made; Subekti , Imam (The International Journal of Accounting and Business Society, 2024)
Purpose — The research aims to empirically test the role of intrinsic motivation in mediating the influence of auditor characteristics on audit quality. The use of intrinsic motivation as a mediation variable is intended to clarify the influence of the various individual characteristics of a particular auditor on the quality of the results of the audit work. Design/methodology/approach — The study was conducted on 110 auditors from various Public Accounting Offices using the snowballing survey approach and Partial Least Squares (PLS) analysis with the help of Smartpls 3.2.9. Findings — The research finds that intrinsic motivation is influenced by the knowledge and independence of the auditor and, consequently, that internal motivation, knowledge, and independence of the auditors affect the audit quality. The study also demonstrated that the intrinsic motivation of auditors has a low influence in mediating the influence of audit knowledge on the audit quality and that the auditor's instrumental motivation tends to have a moderate influence on mediating the relationship of independence with the audit authority. Furthermore, it was found that audit experience did not affect the intrinsic motivation and quality of the audit. Practical implications—Based on the findings, auditors and public accounting firms are advised to reevaluate the quality of their audit through knowledge, independence, and intrinsic motivation. The results of this empirical research have successfully demonstrated that the audit quality is improved by influencing the characteristic audit resource quality. Professional knowledge and independence with the mediation of intrinsic motivation, although its influence is still low and moderate. Originality/value — The findings support the development of the self-determination theory in explaining the role of the human capital theory as justification for the influence of auditor characteristics in improving the quality of their audit. Keywords: Knowledge, experience, independence, intrinsic motivation, and audit quality. Paper type — Research Paper